Development of binderless particleboard from kenaf core using steam-injection pressing - Xu, Jianying; Han, Guangping; Wong, E.D.; Kawai, Shuichi (The Japan Wood Research Society, 2003)
Binderless particleboards were successfully developed from kenaf core using the steam-injection press. The effects of board density, steam pressure, and treatment time on the properties of the board were evaluated. The target board densities were relatively low, ranging from 0.40 to 0.70g/cm3. The properties [i.e., moduli of rupture (MOR) and elasticity (MOE) in both dry and wet conditions, internal bonding strength (IB), and water absorption (WA)] of the boards increased linearly with increasing board density. Steam pressure and treatment time also affected the board properties. The bending strength and IB were improved with increased steam pressure. A long steam treatment time contributed to low thickness swelling (TS) values and thus better dimensional stability. The appropriate steam pressure was 1.0 MPa, and the treatment time was 10-15min. The properties for 0.55g/cm3 density boards under optimum conditions were MOR 12.6MPa, MOE 2.5 GPa, IB 0.49MPa, TS 7.5%, and wet MOR 2.4MPa. Compared with the requirement of JIS 5908.1994 for particleboard, kenaf binderless boards showed excellent IB strength but relatively poor durability.